Total cost comparison in relapsed/refractory multiple myeloma. (May 2013) - Durie, Brian; Binder, Gary; Pashos, Chris; Khan, Zeba; Hussein, Mohamad; Borrello, Ivan
Abstract Objectives: Advances in survival in multiple myeloma have focused payer attention on the cost of care. An assessment was conducted to compare the costs of two recent treatments for relapsed/refractory multiple myeloma (rrMM), from the perspective of a US payer. Methods: An economic model estimated the total costs of care for two guideline-recommended therapies in rrMM patients: bortezomib (BORT) and lenalidomide plus dexamethasone (LEN/DEX). To evaluate total treatment costs, the costs associated with drug treatment, medical resource utilization, and adverse event (AE) management were determined for each regimen over a common 1-year period. Medical costs and grade 3/4 AE costs were based on rates from published literature, package inserts, and fee schedules (US dollars). To evaluate cost per outcome, assessments determined the monthly costs without disease progression based on pivotal clinical trials (APEX [BORT] and MM-009/MM-010 [LEN/DEX]). Univariate sensitivity analyses and alternative scenarios were also conducted. Results: Drug costs for the treatments were very similar, differing by under $10 per day. Medical and AE management costs for BORT were higher by more than $40 per day. Treatment with BORT had annual excess total costs of >$17, 000 compared with LEN/DEX. A cost advantage for LEN/DEX was maintained across a variety of sensitivity analyses. Total cost per month without progression was 11% lower with LEN/DEX. Limitations: This analysis relied on separate studies having similar comparators, populations, and end-points. Actual treatment patterns and costs pre- and post-relapse may vary from the base scenario and sensitivities modeled. The 12-month time frame captures the preponderance of costs for a relapse line of therapy, yet may not reflect the entirety of costs. There is insufficient evidence to determine whether, or how, a difference in the lifetime costs of the two regimens would vary from the 1-year cost difference. Conclusion: While rrMM treatment with BORT and LEN/DEX had comparable drug costs, total treatment costs for BORT were higher due to ongoing direct medical and AE management costs. Total costs per outcome (a month without disease progression) were lower for LEN/DEX.